2020
DOI: 10.1186/s40537-020-00355-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Big Data-machine learning models for diabetes prediction and flight delays analytics

Abstract: Introduction Nowadays large data volumes are daily generated at a high rate. Data from health system, social network, financial, government, marketing, bank transactions as well as the censors and smart devices are increasing. The tools and models have to be optimized. In this paper we applied and compared Machine Learning algorithms (Linear Regression, Naïve bayes, Decision Tree) to predict diabetes. Further more, we performed analytics on flight delays. The main contribution of this paper is to give an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It was observed that 58% of the reviewed papers [15, were based on BD predictive analytics, 18% BD prescriptive analytics [103][104][105] , 11% BD descriptive analytics [15, , whiles 9% (A+B) [100][101][102][103][104][105] and 5% (B+C) [106][107][108] . Few studies in BDA used prescriptive analytics (see Table A1 in Appendix); this can be attributed to fact that big data prescriptive analytics is in its early stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that 58% of the reviewed papers [15, were based on BD predictive analytics, 18% BD prescriptive analytics [103][104][105] , 11% BD descriptive analytics [15, , whiles 9% (A+B) [100][101][102][103][104][105] and 5% (B+C) [106][107][108] . Few studies in BDA used prescriptive analytics (see Table A1 in Appendix); this can be attributed to fact that big data prescriptive analytics is in its early stage.…”
Section: Methodsmentioning
confidence: 99%
“…ML algorithm's hybridisation is an excellent technique to compensate for the weakness in the individual algorithm [9] . However, it was revealed that few studies out of 66 papers reviewed adopted it [70,83,85,88,101,102,107,108,118,122] . From Fig.…”
Section: Big Data Platforms Tool In Bdamentioning
confidence: 99%
“…The experimental results show that SVM achieved the highest accuracy, which is 77.73%. Nibareke & Laassiri (2020) compared DT, LR, and NB classifiers on Vincent Sigillitan’s data set. This work aims to overview machine learning modeling and big data tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Opperhuizen and Schouten [81] 2021 Media √ √ Issue attention analysis Liu et al [73] 2021 Environmental monitoring √ √ Mapping Sharma and Gupta [82] 2021 Healthcare √ √ Predictive analysis Kovacs-Györi et al [83] 2020 Urban planning √ √ Geospatial analysis Nibareke and Laassiri [84] 2020 Healthcare, aviation √ √ Prediction Hosseini et al [65] 2020 Healthcare √ √ Medication optimization…”
Section: Study Yearmentioning
confidence: 99%